Respons Lingkungan terhadap Perubahan Iklim Keterlibatan Masyarakat Petani Kajian Ilmu Alamiah Dasar dan Islami - Roji , Syarief Ahmad Khoirur; Maulida, Az-Zahra Putri; Meirani, Silmi Kaffah; Suherman, Suherman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to provide an in-depth understanding of the impact of climate change on agricultural yields and identify solutions and strategies that can be applied to maintain agricultural yields amid this global challenge. This research uses the literature study method, presenting it descriptively by analysing, collecting data and scientific information from various sources including books, journals and documents related to the research, the preparation is carried out to explore the object of research and develop a deeper understanding of climate change. The results of the study that climate change has a significant impact on agricultural yields, due to uncertainty in the pattern of summer and rainy seasons, to deal with these circumstances farmers develop strategies, one of which is the selection of crop varieties that are more resistant to extreme conditions and the application of efficient irrigation technology. The conclusion of this study emphasizes that a deep understanding of farmers' responses to climate change is crucial to formulate a more comprehensive approach to agricultural management. With the implementation of appropriate adaptation strategies, it is expected to improve food security and farmers' welfare in the face of global climate change challenges.